2019
DOI: 10.3389/fphar.2019.00470
|View full text |Cite
|
Sign up to set email alerts
|

Trace Amine-Associated Receptor 1 Agonist Modulates Mismatch Negativity-Like Responses in Mice

Abstract: The trace amine-associated receptor 1 (TAAR1) is a G protein-coupled receptor widely expressed in the mammalian brain, particularly in limbic system and monoaminergic areas. It has proven to be an important modulator of dopaminergic, serotoninergic, and glutamatergic neurotransmission and is considered to be a potential useful target for the pharmacotherapy of neuropsychiatric disorders, including schizophrenia. One of the promising schizophrenia endophenotypes is a deficit in neurocognitive abilities manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Indeed, in our study, we observed significant alterations in various measures of anxiety and affectivity of TAAR5-KO mice in a number of behavioral tests used to test putative anxiolytic and antidepressant drugs. Importantly, the lack of TAAR5 results in the anxiolytic/antidepressant-like phenotype, while recently identified putative nonselective TAAR5 receptor agonist 2-(alpha-naphthoyl) ethyltrimethylammonium iodide (alpha-NETA) increases cortical gamma-rhythm in rats (Belov et al, 2019), causes deficits in sensorimotor gating in rats (Aleksandrov et al, 2018a), and increases mismatch negativity (MMN)-like responses in rats and mice (Aleksandrov et al, 2018b(Aleksandrov et al, , 2019 in a manner consistent with psychosis-related cognitive deficits described in humans and experimental animals (Light and Swerdlow, 2015).…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, in our study, we observed significant alterations in various measures of anxiety and affectivity of TAAR5-KO mice in a number of behavioral tests used to test putative anxiolytic and antidepressant drugs. Importantly, the lack of TAAR5 results in the anxiolytic/antidepressant-like phenotype, while recently identified putative nonselective TAAR5 receptor agonist 2-(alpha-naphthoyl) ethyltrimethylammonium iodide (alpha-NETA) increases cortical gamma-rhythm in rats (Belov et al, 2019), causes deficits in sensorimotor gating in rats (Aleksandrov et al, 2018a), and increases mismatch negativity (MMN)-like responses in rats and mice (Aleksandrov et al, 2018b(Aleksandrov et al, , 2019 in a manner consistent with psychosis-related cognitive deficits described in humans and experimental animals (Light and Swerdlow, 2015).…”
Section: Discussionmentioning
confidence: 86%
“…Particularly deficits in MMN are believed to reflect cognitive decline and have been associated with glutamatergic NMDA receptor alterations [139,142]. In naïve mice, ulotaront and RO5263397 increase PPI and MMN, respectively [120]. Whether TAAR1 agonists can reverse impairments in PPI and MMN (e.g., in rodent models of schizophrenia) remains to be investigated.…”
Section: Role Of Taar1 In Cognition Negative Symptoms Mood and Anxietymentioning
confidence: 99%
“…α-NETA, an inhibitor of acetyl-cholinesterase, potently activates TAAR5, and displays interesting in vivo properties in mice and rats, inducing psychotic-like states and influencing cortical parameters related to cognitive functions [25,26,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Although with lower potencies, two other tertiary amines activate TAAR5, namely N-N-dimethylethylamine and N-methylpiperidine [ 5 ]. α-NETA, an inhibitor of acetyl-cholinesterase, potently activates TAAR5, and displays interesting in vivo properties in mice and rats, inducing psychotic-like states and influencing cortical parameters related to cognitive functions [ 25 , 26 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%